2021
DOI: 10.3390/diagnostics11020195
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Left Subclavian Artery-Esophageal Fistula in a Patient with a Prolonged Use of Nasogastric Tube: A Case Report and Literature Review

Abstract: Arterial-esophageal fistula is a rare but potentially fatal complication. Right aortic arch with aberrant left subclavian artery is a rare congenital vascular anomaly that can cause esophageal compression, particularly when the proximal portion of the aberrant subclavian artery forms a Kommerell’s diverticulum. Prolonged use of a nasogastric tube can cause pressure necrosis of the esophagus. We report a patient with massive gastrointestinal bleeding secondary to aberrant left subclavian artery-esophageal fistu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Based on medical history, physiological signs, examination and treatment, this case of delayed but high-risk massive upper GI bleeding was the result of a fish bone piercing the esophagus, causing the mediastinal abscess that corroded the LSA. Fistulas between the subclavian artery and esophagus are rare but can rapidly become life-threatening [ 12 , 13 ]. Clinically, among arterial-esophageal fistulas caused by esophageal foreign bodies, the proportion of LSA esophageal fistulas is only 2% [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on medical history, physiological signs, examination and treatment, this case of delayed but high-risk massive upper GI bleeding was the result of a fish bone piercing the esophagus, causing the mediastinal abscess that corroded the LSA. Fistulas between the subclavian artery and esophagus are rare but can rapidly become life-threatening [ 12 , 13 ]. Clinically, among arterial-esophageal fistulas caused by esophageal foreign bodies, the proportion of LSA esophageal fistulas is only 2% [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…2 Prolonged endotracheal and/or nasogastric intubation is the most common predisposing factor for fistula formation. On literature review, we found a total of 17 cases of aberrant subclavian artery–esophageal fistula in which the prolonged endotracheal and/or nasogastric intubation has been listed as a causative factor of fistula formation 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 ( Table 1 ). The average duration between NGT and endotracheal tube (ET) placement and first episode of bleeding is of 29 (6–56) and 23 (13–31) days, respectively.…”
Section: Discussionmentioning
confidence: 99%
“… 20 In few cases, initial “alarming” episodes of minimal bleeding have also been reported. 7 9 10 19 21 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,11,12 Formation of an arterio-esophageal fistula is a dreadful complication of a degenerated Kommerell diverticulum/aneurysm. Kim et al 13 found 40 cases of arterio-esophageal fistula-mainly caused by prolonged use of a nasogastric or endotracheal tube-in their literature review and reported a mortality rate of 60%. There are no surgical guidelines for the management of a Kommerell aneurysm.…”
mentioning
confidence: 99%